Analysis of the implementation of capitation policy based on service commitment at Social Security Agency on Health, Semarang-Indonesia - Dian Ratna Pertiwi; Antono Suryoputro; Matheus Sakundarno Adi (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Performance-based capitation payments are an innovative approach in the health financing system implemented by Social Security Agency on Health (BPJS Health). Purpose: To analyze of the implementation of capitation policy based on service commitment. Method: A descriptive qualitative approach with a case study approach, which aims to analyzing the implementation of the Performance-Based Capitation policy, by taking four variables that are considered most crucial in determining the success of the implementation of the Performance-Based Capitation policy in the city of Semarang, with the policy implementation model approach from Donald Van Meter and Carl Van Horn, namely communication factors, resources, implementer disposition, and implementer characteristics. Results: This approach aims to stimulate the provision of higher quality and more efficient health services, by providing incentives to health service providers based on optimal performance and service outcomes. The implementation of performance-based capitation payments provides several benefits, including increased accountability of health service providers, more effective cost management, and stimulation of innovation in service provision. Conclusion: Performance-based capitation payments by BPJS Health are a step forward in creating a health insurance system that focuses on service quality. Performance-based capitation payments by BPJS Health are a step forward in creating a health insurance system that focuses on service quality.